The Cross-Talk between Spirochetal Lipoproteins and Immunity - Kelesidis, Theodoros (Frontiers in Immunology, 2014)
Spirochetal diseases such as syphilis, Lyme disease and leptospirosis are major threats to public health. However the immunopathogenesis of these diseases has not been fully elucidated. Spirochetes interact with the host through various structural components such as lipopolysaccharides (LPS), surface lipoproteins and glycolipids. Although spirochetal antigens such as LPS and glycolipids may contribute to the inflammatory response during spirochetal infections, spirochetes such as Treponema pallidum and Borrelia burgdorferi lack LPS. Lipoproteins are most abundant proteins that are expressed in all spirochetes and often determine how spirochetes interact with their environment. Lipoproteins are proinflammatory, may regulate responses from both innate and adaptive immunity and enable the spirochetes to adhere to the host or the tick midgut or to evade the immune system. However, most of the spirochetal lipoproteins have unknown function. Herein, the immunomodulatory effects of spirochetal lipoproteins are reviewed and are grouped into two main categories: effects related to immune evasion and effects related to immune activation. Understanding lipoprotein-induced immunomodulation will aid in elucidating innate immunopathogenesis processes and subsequent adaptive mechanisms potentially relevant to spirochetal disease vaccine development and to inflammatory events associated with spirochetal diseases.